2006
DOI: 10.1016/j.jasms.2006.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for high speed quantitative mass spectrometry with MALDI ionization

Abstract: A MALDI ion source on a triple quadrupole mass spectrometer constructed for the purpose of obtaining high speed quantitative measurements on drugs and other low molecular weight compounds is described. Particular attention is given to the ion generation and transport phenomena that affect analysis speed, throughput, and practical instrument robustness. In this regard parameters that affect desorption speed, beam spreading, ion flight times, sensitivity, signal-to-noise, ion fragmentation, sample carry-over, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 25 publications
(39 reference statements)
2
52
0
Order By: Relevance
“…7 This is evident, for example, in the increasing use of matrix-assisted laser desorption/ionization (MALDI) systems to perform routine quantitation; [8][9][10] impressive high-throughput (20 samples/min) data have been reported. 11 Two former limitations of this experiment, strong matrix interference in the low molecular mass range (< m/z 500) and poor reproducibility of the signal intensities, now appear to be solved by using MS/MS and averaging multiple analyses of the same spot using appropriate an internal standard 12 (IS),…”
mentioning
confidence: 99%
“…7 This is evident, for example, in the increasing use of matrix-assisted laser desorption/ionization (MALDI) systems to perform routine quantitation; [8][9][10] impressive high-throughput (20 samples/min) data have been reported. 11 Two former limitations of this experiment, strong matrix interference in the low molecular mass range (< m/z 500) and poor reproducibility of the signal intensities, now appear to be solved by using MS/MS and averaging multiple analyses of the same spot using appropriate an internal standard 12 (IS),…”
mentioning
confidence: 99%
“…The upper mass range of analytes that can be ionized using R575 visible-MALDI remains unknown due to the limited mass range of our quadrupole mass spectrometer. Based on our current evaluation, binary mixtures containing R575 produce very few chemical fragments, which makes them attractive for the analysis of small molecular weight organic compounds [14,15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the instrument is based on Applied Biosystems/MDS SCIEX API-365 LC/MS/MS triple quadrupole (QqQ) mass spectrometer originally configured for electrospray ionization (ESI) and now equipped with a homemade MALDI ion source, which has been described in reference [14]. The spectra obtained from our MALDI mass spectrometer using UV (337 nm irradiation) were compared with those obtained using a commercial instrument (Bruker Reflex IV).…”
Section: Methodsmentioning
confidence: 99%
“…Although the mass range of a quadrupole instrument is smaller than that of a time-of-flight (TOF) mass spectrometer, it has been shown that MALDI using a QqQ mass spectrometer is well suited for the rapid quantitative measurement of small molecular weight drug molecules with minimal loss in mass resolution or accuracy for non-homogeneous samples [9] because it allows only the ions of interest to be transmitted for detection, thereby limiting matrix signal interferences.…”
Section: Methodsmentioning
confidence: 99%